Understanding the learning that occurs through up-skilling opportunities and practices in the marine sector of South Africa - Bell, Caroline Margaret (Rhodes University, Faculty of Education, Department of Environmental Learning Research Centre, 2019)
South Africa is characterised by cultural and biological diversity which constitute a unique context in which to conduct educational research, such as this doctoral study looking at human capital development in the marine biodiversity context. The drive for transformation in the country is also a major factor to consider when researching any sector of the economy, in this case, the biodiversity sector. The biodiversity sector includes organisations involved in biodiversity conservation, research and management. Previous research in the sector has found a clear need for well-thought out workplace skills plans within conservation and research organisations. The national Biodiversity Human Capital Development Strategy that was produced in 2010 by the South African National Biodiversity Institute outlines how all the organisations involved in the biodiversity sector of South Africa need to participate in strengthening the sector through a range of human capital development strategies. This includes extending the existing human capacity of managers and scientists who are already in the workplace, i.e. up-skilling. In particular, 'scarce' skills, as identified by the national Environmental Sector Skills Plan need further attention and development. The scarce skills relevant to this study are: protected area managers; ecosystem managers and post-graduate researchers, hence the focus on managers and scientists in this research. The marine sector falls within the biodiversity sector and it faces multiple conservation challenges which are complex and it is therefore essential to have skilled and capable managers and scientists in place. By investigating the up-skilling opportunities and practices available to these marine professionals, the goal is to understand if and how learning takes place in the marine sector of South Africa. The main research question of this study is: How do up-skilling opportunities and practices enable learning in, through and for the workplace, by marine professionals? In addition, three sub-questions provide finer details and introduce the central concepts of the research: I. What up-skilling opportunities and professional practices exist in or for, marine research and conservation organisations and how are they constituted and enacted via practice-based sayings, doings and relatings? II. How do the individuals learn and exercise their agency within the socio-material realities of the marine scientific and management context, through making use of up-skilling opportunities that are both formal (e.g. course based) and informal? III. How do generative mechanisms shape the constitution and enactment of up-skilling opportunities and practices, and the learning and agency of marine professionals (scientists and managers)? The theoretical work of this study consisted of, first, considering sensitising concepts which included: defining skill and knowledge; considering what an up-skilling opportunity might look like; workplace learning (both formal and informal learning); professional practices, lifelong learning or adult education, and agency in the workplace. Critical realism was then employed as the meta-theory that underlabours this research, while the substantive theories used for analysis purposes were socio-materialism and practice theory. Of course, critical realism is a socio-material theory itself, and Bhaskar's four-planar social being or Social Cube was used to interpret and synthesise the findings in the data chapters. The methodological framework of this study explores the implications of critical realism for research design and analysis and includes a contextual profiling phase, semi-structured interviews, analysis of documents and peer-reviewed papers, as well as observations. There are nine case studies that form the focus of this research and in total 18 research participants were involved. Data analysis included abduction and retroduction as the primary modes of inference and the main analytical tool was the framework of practice architectures where I took the 'sayings', 'doings' and 'relatings' as themes. Further themes were developed from the other relevant theories used in this study; hence socio-materialism, learning, agency, and formal and informal opportunities, were also used as themes when coding the data. Issues around validity, ethics and reflexivity are key elements of the research design and were carefully considered throughout the research process. The principal data chapters are structured in such a way that each sub-question is considered and ultimately the findings are presented in the form of generative mechanisms which included: the politics of social transformation and knowledge as a driving force of up-skilling; the influence of individual disposition and passion or will; the importance of the socio-material realities and realistic expectations; and how relationality is critical for the marine sector. Agency was a cross-cutting theme in all the discussions around learning, practices and the role of the material, and was highly influential on the mechanisms that have been described in this study. The experiences, events and mechanisms that were uncovered in this research provide insight into the forms of learning as these relate to up-skilling that occur in the marine sector, as well as the complex relationships between formal and informal learning. The professional practices that occur in the everyday working lives of the marine professionals were shown to be an integral part of the learning process, while formal, certified opportunities are important for strengthening the field and building conservation competence in the country. By uncovering the deeper structures and mechanisms that have power and causal efficacy when it comes to up-skilling opportunities, learning and professional practices, this study has contributed to the field of environmental education as it shows how up-skilling processes operate in complex formations that involve formal and informal learning processes in workplaces. The study also offers a more nuanced view of the relational objects in this field, such as up-skilling and workplace learning, via the inclusion of a socio-material analysis. Through a theoretical and methodological framework that focused on the material using the tools of practice theory and Bhaskar's depth ontology and four-planar social being (to synthesise and interpret the findings from a critical realist perspective), this research highlights the unique context of up-skilling opportunities and practices in the marine sector and reveals the crucial role of agency in workplace practices. This leads to a better understanding of the up-skilling opportunities and practices of marine professionals in South Africa, which ultimately contributes towards improved human capital development in the biodiversity and environmental sectors. Through offering more complex insights into the forms of learning and up-skilling, as well as a distinct methodological contribution, this research has broader relevance for workplace learning research.
Keywords: Biodiversity conservation -- South Africa; Human capital -- South Africa; Marine sciences -- Employees -- South Africa -- Training of; Biodiversity Human Capital Development Strategy (South Africa)